Numerical simulation of 3D transonic flow in a compressor rotor - Ng K.C.; Yusoff M.Z.; Yusaf T.F. (Acta Press, 2023)
This paper presents a new computational fluid dynamics (CFD) code developed at Universiti Tenaga Nasional for the numerical computation of transonic laminar flow in a compressor rotor. The 3D computational code solves the unsteady Navier-Stokes equations (NSE) on unstructured hexahedral mesh by using second-order accurate central differencing scheme on both convective and diffusive terms. Artificial damping terms are added to control the stability of the numerical scheme, and the explicit multistage Runge-Kutta time-integration technique is performed to solve the unsteady NSE. This paper discusses the simulation of compressible flow field in an axial-flow compressor rotor using the newly developed CFD code. The predicted flow is then compared with the results obtained from the commercial code, CFX-5, as well as experimental data; good agreement is found.